Single Organoids Droplet-Based Staining Method for High-End 3D Imaging of Mammary Organoids - Sumbal, Jakub; Koledova, Zuzana (Methods in molecular biology, 2022)
In the last decade, organoids became a tremendously popular technique in developmental and cancer biology for their high pathophysiological relevance to in vivo models with the advantage of easier manipulation, real-time observation, potential for high-throughput studies, and reduced ethical issues. Among other fundamental biological questions, mammary organoids have helped to reveal mechanisms of mammary epithelial morphogenesis, mammary stem cell potential, regulation of lineage specification, mechanisms of breast cancer invasion or resistance to therapy, and their regulation by stromal microenvironment. To exploit the potential of organoid technology to the fullest, together with optimal organoid culture protocols, visualization of organoid architecture and composition in high resolution in three dimensions (3D) is required. Whole-mount imaging of immunolabeled organoids enables preservation of the 3D cellular context, but conventional confocal microscopy of organoid cultures struggles with the large organoid sample size and relatively long distance from the objective to the organoid due to the 3D extracellular matrix (ECM) that surrounds the organoid. We have overcome these issues by physical separation of single organoids with their immediate stroma from the bulk ECM. Here we provide a detail protocol for the procedure, which entails single organoid collection and droplet-based staining and clearing to allow visualization of organoids in the greatest detail.
Keywords: Organoids; zobrazování trojrozměrné; Microscopy, Confocal; Breast; Staining and Labeling; lidé; prsy; Imaging, Three-Dimensional; Humans; barvení a značení; konfokální mikroskopie; organoidy